Assessing water-energy nexus dynamics for sustainable resource management in Cape Town : a system dynamics approach - Ndlela, Thandekile Julianah (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.